Antibacterial Activity of Cuttlefish Sepia sp. (Cephalopoda,) Ink Extract Against Aeromonas hydrophila - R Adharyan Islamy (Majalah Obat Tradisional, 2019)
Cephalopods ink has shown potential antiretroviral activity. The ink extracts of cuttlefish showed an antibacterial effect. This study aims to investigate the antibacterial activity of the methanolic extract of the ink of cuttlefish Sepia sp. against Aeromonas hydrophila. A. hydrophila are opportunists and associated with aquatic fish and shrimp disease. The shade-dried ink sample from approximately 30g ink sacs obtained from 15 animals was immersed separately in methanol (1:3 w/v) solvents for overnight. The experiment in this study used the dried extract of cuttlefish ink. The isolate of A. hydrophila was originated from Jepara Brackishwater Aquaculture Center. The average yield percentage of cuttlefish ink extract obtained was 4.86%. The results of the MIC test in Table V show that the highest average absorbance value obtained was at a concentration of 50 ppm, which was equal to 1.716 nm, and the lowest absorbance was obtained at a treatment dose of 300 ppm at 0.841 nm, while the Mc Farland tube was 0.933 nm. The results of antibacterial test on Table II showed antibacterial activity of cuttlefish ink extract at negative concentration control showed diameter zone of 5 ± 1.2 mm, at positive control showed diameter zone of 31 ± 1.2 mm, at 250 ppm result 19 ± 0.9 mm, at 300 ppm result 22 ± 1.4 mm, at 350 ppm result 31 ± 1.2 mm.